Adenomyosis in Pakistani women: four year experience at the Aga Khan University Medical Centre, Karachi. - Shaikh, H (1990)
As part of a quality assurance programme at the Aga Khan University Medical Centre, Karachi, Pakistan, all hysterectomy specimens were reviewed from January 1986 to December 1989. Adenomyosis was found in 237 of the 419 (56.5%) specimens studied. Of these 237 patients, 232 (97.9%) were parous and 196 (82.8%) were in the fourth and fifth decades of life. This high prevalence in parous women aged 40-59 years was significant. Fibroids, cervicitis, and endometrial hyperplasia were the most common associated diagnoses. Of all the associations studied, only endometrial hyperplasia was significantly more prevalent in the group with adenomyosis. Adenomyosis was stated as an indication for surgery in 69 patients and was confirmed by histopathology in 49 (71%). Preoperative suspicion of adenomyosis was present in 49 (20.6%) patients of all those ultimately found to have the disease. There is a high prevalence of adenomyosis in the population studied, which indicates that the condition may have been underdiagnosed in the past, especially as it is difficult to diagnose without surgery and hysterectomy is currently the only treatment.